Neurological Nuance: Hodgkin lymphoma presenting with Guillain–BarrÉ syndrome. Issue 4 (9th November 2016) - Anderson, Dustin; Beecher, Grayson; Steve, Trevor A.; Jen, Ho; Camicioli, Richard; Zochodne, Douglas W.
ABSTRACT: Introduction: Hodgkin lymphoma (HL) is a common lymphoid malignancy rarely associated with Guillain–Barré syndrome (GBS). In most cases, GBS does not precede HL. Methods: We describe a patient with acute inflammatory demyelinating polyneuropathy who fulfilled criteria for GBS that heralded undiagnosed HL. Results: Cerebrospinal fluid (CSF) studies revealed albuminocytologic dissociation with significant protein elevation (250 mg/dl). The patient worsened during intravenous immunoglobulin (IVIg) therapy. Constitutional symptoms with elevated inflammatory markers prompted further investigation, and imaging revealed an anterior mediastinal mass confirmed on biopsy to be HL. Chemotherapy yielded early clinical improvement. Conclusions: GBS preceding HL is rare, and this case highlights the importance of considering HL in the setting of GBS. Marked elevations in CSF protein, ongoing deterioration despite administration of IVIg, and constitutional symptoms with elevated inflammatory markers may be clues to possible HL‐induced GBS. Muscle Nerve 55 : 601–604, 2017